MENINGKATKAN KEMAMPUAN BELAJAR SISWA DALAM PERMAINAN SEPAK BOLA DENGAN PENDEKATAN SHOOTING COLOUR - Rahayu Asih (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
The students’ compentence of VIIA SMP Negeri 2 Muara Bungo in playing football was still low. Thai’swhy this research was aimed to describe the implementation of shooting colour approach in increasing this competence. The research is class room action researh that thirty students of VII.A as the subject of the research. The research was designed into two cycles. Each cycle consist of four phases. They are planning, doing, observing and reflecting. The research used observation sheet and field note as the instrument in collecting the data. The result of the research showed that the students’ competence in playing football was inreased from cycle I to the cycle II after applying shooting colour approach. It can be seen from the advanced of students ability in kicking, dribbling, heading, throwing in, tackling and stopping the ball.The research was not only able to increase the students competency but also given positive effect in increasing motivation and enthusiasm in learning sport.